Involvement of polyamines in creasing of sweet orange [Citrus sinensis (L.) Osbeck] fruit - Hussain, Z.; Singh, Zora (Elsevier, 2015)
Creasing is a physiological disorder in the rind of sweet orange [. Citrus sinensis (L.) Osbeck] fruit and causes serious economic losses in the world. The involvement of polyamines in creasing and rind thickness of sweet orange fruit was investigated employing exogenous applications of putrescine (PUT) and a reversible inhibitor of polyamine biosynthesis (guanylhydrazone; MGBG) at different fruit developmental stages through regulating endogenous levels of free PUT, spermidine (SPD), spermine (SPM) and total polyamines in albedo and flavedo tissues of the fruit. A spray application of PUT depending upon its concentration and time of application reduced creasing index percent (CI) and increased rind thickness in Washington Navel and Lane Late fruit during 2011 and 2012. Single spray of PUT (500-1000. µM) applied at fruit set or golf ball stage was more effective in reducing CI as compared to all other treatments, in both the cultivars. PUT applied at fruit set, golf ball or mature fruit stage resulted in increased levels of endogenous free polyamines (PUT, SPD, SPM and total free polyamines) in the flavedo and albedo tissues of fruit in both cultivars. Single spray application of MGBG (1000. µM) at the golf ball stage significantly increased CI in Washington Navel and Lane Late orange fruit. In conclusion, these results suggest the involvement of polyamines in creasing of sweet orange fruit.